An efficient partial synthesis of 4′-O-methylquercetin via regioselective protection and alkylation of quercetin - Li, Nian-Guang; Shi, Zhi-Hao; Tang, Yu-Ping; Yang, Jian-Ping; Duan, Jin-Ao (Beilstein Journal of Organic Chemistry, 2009)
An efficient partial 5-step synthesis of 4′-O-methylquercetin from quercetin in 63% yield is reported. This strategy relies on the selective protection of the catechol group with dichlorodiphenylmethane in diphenyl ether as solvent and on the selective protection of the hydroxyl groups at positions 3 and 7 with chloromethyl ether.
Keywords: alkylation; high yield; 4′-O-methylquercetin; partial synthesis; regioselective protection